Antiproliferative Effect of The Bark and Leaves of Erythrina Fusca Lour Against HeLa Cells - Meiyanto, Edy; ., Sismindari,; Candra, Lany; ., Moordiani (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
Erythrina fusca Lour (Indonesian: Cangkring) has been traditionally used to cure skin virus infection, cancer and inflammation. This experiment, therefore, was conducted to test its ability as anticancer through its antiproliferative effect using HeLa examine cell line as model. The bark and leaves powder were extracted using ethanol (70 %) and were used in the experiment after freezed drying. Those bark and leaves extracts have LC50 values of 110 and 140 mg/ml respectively. Antiproliferative effect was tested by examining the doubling time effect of the extract against the proliferating cells. Three different concentration were used to treat the cells for each extract, and cells were counted within time courses. The growth profiles were then compared between treated and control cells by calculating the doubling times. Either bark and leaves extract treated cells showed prolongation of the doubling times. This result indicated that such extract possess inhibitory effect or Antiproliferative effect against HeLa cells. Morphology analysis and nuclear staining of the cells indicated that one of the mechanism of the antiproliferative effect possibly through cell cycle modulation and apoptotic pathway. Keywords: Erythrina fusca, Antiproliferative, Doubling time, HeLa Cell